The Influence of Price Perception and Product Quality on Repurchase Decision through Customer Satisfaction as an Intervening Variable at Pizza Hut Restaurant, Palangka Raya Branch - Meidian Krisna, Kade Chrysti; Kristinae, Vivy; Meitiana, Meitiana; Syamsudin, Achmad (Institute of Computer Science (IOCS), 2025)
This study aims to examine the influence of price perception and product quality on repurchase decisions, with customer satisfaction as an intervening variable, at the Pizza Hut branch in Palangka Raya. The subjects of this research are customers who have previously visited and made purchases at the aforementioned branch. A total of 112 respondents were selected using purposive sampling techniques. Data collection was conducted by directly distributing questionnaires to the respondents. The analytical method employed is Partial Least Squares (PLS), which is used to test and evaluate the relationships among variables within the model. The findings indicate that price perception has a significant effect on repurchase decisions. However, price perception does not have a significant impact on customer satisfaction. This suggests that price is not always the primary determinant of customer satisfaction levels. Other factors, such as product quality, perceived value, brand reputation, customer experience, economic conditions, market competition, technological changes, and perceived product value, may also influence consumer purchasing decisions. On the other hand, product quality is found to have a significant influence on both customer satisfaction and repurchase decisions. These findings underscore the importance for companies to consistently maintain and improve product quality in order to sustain customer loyalty